2006
DOI: 10.1055/s-2006-925390
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and Prolactin, but not Corticosterone, Modulate Body Weight and Thyroid Function in Protein-malnourished Lactating Rats

Abstract: To understand the role of hormonal changes in the lower food ingestion and body weight in protein-restricted lactating rats as well as the higher serum T (3), higher deiodination, iodide and T (3) milk transfer, we measured maternal serum prolactin, leptin, TSH and corticosterone, which are hormones that could influence those parameters. After birth, dams were separated into: control-fed with a 23 % protein diet (n = 12) and PR (protein-restricted)-fed with an 8 % protein diet (n = 12). At the 4 (th) and 21 (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
31
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…We found that during lactation, maternal nutrition can program body weight (15)(16)(17)(18)(19)(20)(21)31) and thyroid function (7,13) of their offspring in adult life. So, reinforcing our previous report, the present study provides evidence that maternal protein restriction, during lactation, programs others parameters of the thyroid function in the adult offspring, which helps in understanding observed hyper-thyroidism.…”
Section: Discussionmentioning
confidence: 93%
“…We found that during lactation, maternal nutrition can program body weight (15)(16)(17)(18)(19)(20)(21)31) and thyroid function (7,13) of their offspring in adult life. So, reinforcing our previous report, the present study provides evidence that maternal protein restriction, during lactation, programs others parameters of the thyroid function in the adult offspring, which helps in understanding observed hyper-thyroidism.…”
Section: Discussionmentioning
confidence: 93%
“…In terms of body weight regulation, hyperprolactinemia in men and nonpregnant women may be accompanied by weight gain (Sobrinho, 2003). Inhibition of PRL function by bromocryptine (Lisboa et al, 2006; Bonomo et al, 2007, 2008; de Moura et al, 2009) and knockout of the PRL gene (Freemark et al, 2001) have also been reported to induce changes in food intake, weight gain, and/or body fat metabolism, although the outcomes differed depending on the species, sex, and timing of exposure. The results of our and earlier studies address the possibility that PRL may play a critical role in IS‐induced metabolic programming.…”
Section: Discussionmentioning
confidence: 99%
“…This result was expected due to the lower maternal PR diet intake until weaning. It is known that PR lactating dams present hypophagia and it may be caused by the combination of hyperleptinemia and hypoprolactinemia [14] , once leptin is anorexigenic and PRL is orexigenic. Those PRL changes explain the milk protein deficiency and lower volume.…”
Section: Discussionmentioning
confidence: 99%